Effect of retinoic acid and palm oil carotenoids on oestrone sulphatase and oestradiol-17β hydroxysteroid dehydrogenase activities in MCF-7 and MDA-MB-231 breast cancer cell lines - Ng, Jin-Huat; Nesaretnam, Kalanithi; Reimann, Karin; Lai, Leslie C. (Wiley, 2000)
Oestrogen is important in the development of breast cancer. Oestrogen receptor positive breast cancers are associated with a better prognosis than oestrogen-receptor negative breast cancers since they are more responsive to hormonal treatment. Oestrone sulphate acts as a huge reservoir for oestrogens in the breast. It is converted to the potent oestrogen, oestradiol (E2) by the enzymes oestrone sulphatase and oestradiol-17β hydroxysteroid dehydrogenase (E2DH). Retinoic acid and carotenoids have been shown to have chemopreventive activity against some cancers. The aim of our study was to determine and compare the effects of retinoic acid and palm oil carotenoids on growth of and oestrone sulphatase and E2DH activities in the oestrogen receptor positive, MCF-7 and oestrogen receptor negative, MDA-MB-231 breast cancer cell lines. Retinoic acid and carotenoids inhibited MCF-7 cell growth but had no effect on MDA-MB-231 cell growth. Both retinoic acid and carotenoids stimulated oestrone sulphatase activity in the MCF-7 cell line. E1 to E2 conversion was inhibited by 10(-7) M carotenoids but was stimulated at 10(-6) M in the MCF-7 cell line. Retinoic acid had no effect on E1 to E2 conversion at 10(-7) M but stimulated E1 to E2 conversion at 10(-6) M. Retinoic acid and carotenoids had no effect on E2 to E1 conversion in the MCF-7 cell line. Retinoic acid stimulated E1 to E2 conversion in the MDA-MB-231 cell line but had no effect on oestrone sulphatase activity or E2 to E1 conversion in this cell line. Both oestrone sulphatase and E2DH activity were not affected by carotenoids in the MDA-MB-231 cell line. In conclusion, retinoic acid and carotenoids may prevent the development of hormone-dependent breast cancers since they inhibit the growth of the MCF-7 cell line.